Factors influencing cross-border shopping / Azila Azmi, Monica Easter Ak Sapi@Chikut and Sharifah Munirah Sayed Abdul Rahman - Azmi, Azila; Sapi@Chikut, Monica Easter; Sayed Abdul Rahman, Sharifah Munirah (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2015)
This concept paper discusses the factors influencing cross-border shopping. This type of shopping activity is already well known nowadays as evidenced by the appearance of many cross-border shopping destinations around the world. Visitors tend to choose cross-border shopping destination as their shopping spot because they can find variety of products and services which include household items, fruits and vegetables, clothes and also handicraft products. The factors influencing cross-border shopping are grouped under consumer characteristics and market characteristics. Consumer characteristics consist of age, gender, marital status, education level, occupation, and average income per month whereby market characteristics consist of lower price, variety of goods, lower tax, accessibility, communication, social status and opening hour. Lower price and variety of goods are the dominant factors for cross-border shopping.